Barriers To The Implementation Of Sustainable Warehousing: A Systematic Literature Review - M. Rizki Gusri; Erna Mulyati; Maniah, Maniah (proceedings.icesy, 2026)
The implementation of sustainable warehousing is an important element in efforts to decarbonize the supply chain and achieve Environmental, Social, and Governance (ESG) goals. Although the environmental, social, and economic benefits of sustainable warehousing practices have been widely reported, the level of implementation is still relatively limited due to various multidimensional obstacles. This study aims to identify and analyze the main factors that hinder the implementation of sustainable warehousing through a Systematic Literature Review (SLR) approach. The review process was conducted using a four-stage protocol with searches on five major scientific databases, namely Scopus, Taylor & Francis, IEEE Xplore, ScienceDirect, and Google Scholar. From a total of 79,116 initial publications, 50 selected articles (from 2020–2025) were analyzed thematically and quantitatively. The results of the study revealed six dominant barriers, namely high initial investment costs (30%), technological and infrastructure limitations (22%), lack of skills and human resource resistance (16%), high energy consumption and dependence on fossil fuels (14%), weak regulations and policy support (10%), and challenges in integrating digital systems such as WMS, IoT, and AI (8%). These findings confirm that the barriers to sustainable warehousing are systemic and interrelated, with economic and technological factors dominating and being significantly influenced by social, energy, and institutional aspects. This research contributes to the enrichment of the logistics sustainability literature by providing a comprehensive mapping of barriers and offering a conceptual basis for the development of holistic, adaptive, and long-term implementation strategies.